Mental Health Status and its Determinants Among Older People in Rural Area in the District of Banyumas Central Java (Association of Public Health Scholars based in Faculty of Public Health, Sriwijaya University, 2023)
Elderly people experience several health problems due to their vulnerability to many diseases, which may affect their mental health. This study aims to assess mental health status among older people and its determinants in rural areas. It is a cross-sectional study design and involves 412 respondents from 9 villages in the district of Banyumas, Central Java, Indonesia. The data was analyzed by using a logistic regression model. The findings showed that older people with a large number of family members were four times more likely to have a mental health problem than those with a small number. Older people with a history of chronic disease had a threefold greater risk of experiencing mental health problems than older people without chronic disease. Three times as many elderly people with middle economic status reported having mental health issues. Older people with lower education have fewer mental health problems compared to older people who graduated from higher education levels. Health check-up was discovered to influence mental health problems, with older people who did checkups even if irregularly having fewer mental health problems than older people who never did. The study concludes that family size, chronic disease history, economic condition, education, and health check-up are determinants of mental health problems in rural Indonesia.